2021
DOI: 10.1007/s00170-021-07162-8
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion-based additive manufacturing of forming and molding tools

Abstract: The production of rapid tools for plastic molding, sheet metal forming, and blanking has always been a critical and important goal for applied research, and a very large number of alternative methods have been proposed over the decades for their production. Among these methods, the use of extrusion-based additive manufacturing (EAM), such as fused filament fabrication (FFF) or similar technologies, has not been frequently considered and needs to be explored extensively. EAM is generally considered a low-cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…They concluded that polymer tools give similar UTS with respect to aluminum tools but lower elongation and brittle fracture. Strano and his coworkers [39] reviewed different types of rapid tools produced by material extrusion, both for sheet deformation and injection molding, including metal tools made by extrusion, debinding and sintering. Farioli and his colleagues [10] studied the effectivity, through DSC, DMA, compression tests, and simulations, of an injection mold produced by filament FDM with PEI 1010.…”
Section: Applicationsmentioning
confidence: 99%
“…They concluded that polymer tools give similar UTS with respect to aluminum tools but lower elongation and brittle fracture. Strano and his coworkers [39] reviewed different types of rapid tools produced by material extrusion, both for sheet deformation and injection molding, including metal tools made by extrusion, debinding and sintering. Farioli and his colleagues [10] studied the effectivity, through DSC, DMA, compression tests, and simulations, of an injection mold produced by filament FDM with PEI 1010.…”
Section: Applicationsmentioning
confidence: 99%
“…These tools can be manufactured from metal alloys or polymers using the AM technology. The existing research has focused on evaluating their flexibility, feasibility and mechanical performance (Strano et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research has shown that The compressive strength and surface finish in fused filament fabrication (FFF) parts play critical roles in various demanding applications. Notably, FFF finds application in metal forming and molding tools [8][9][10], jigs and fixtures [11,12], full-scale molds for wind turbine blades [13], packaging products [14,15], bone scaffolds [2], and medical implants [16], where compressive strength is essential to withstand compressive stresses. The surface finish is equally crucial in such applications.…”
Section: Introductionmentioning
confidence: 99%